[Image 04] - Smith, Captain Sir William [?ob. 1732] (My University, 1810)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of the Cavalier or Keep in the remains of a redout on a hill in the Island of Burt (so called altho not an island) drawn by Sir Wm Smith in 1810. This fortification Sir W. Smith proves to have been found by the Spaniards, in the reign of Queen Elizabeth.
Keywords: Island of Burt; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Landscapes (Representations) 1800-1810